A Randomized Controlled Trial of Two Ready-to-Use Supplementary Foods Demonstrates Benefit of the Higher Dairy Supplement for Reduced Wasting in Mothers, and Differential Impact in Infants and Children Associated With Maternal Supplement Response. Issue 3 (September 2017) - Schlossman, Nina; Brown, Carrie; Batra, Payal; de Sa, Augusto Braima; Balan, Ionela; Balan, Adrian; Gamache, Madeleine G.; Wood, Lauren; Pruzensky, William; Saltzman, Edward; Roberts, Susan B.; Balé, Carlito
Background: There is no consensus over best approaches to reliably prevent malnutrition in rural communities in low-income countries. Objective: We compared the effectiveness of 2 lipid-based ready-to-use supplementary foods (RUSFs) differing in dairy protein content to improve the nutritional status of mothers and at-risk infants and young children in rural Guinea-Bissau. Methods: A 3-month cluster-randomized controlled pilot trial of 2 RUSFs was conducted with 692 mothers and 580 mildly or moderately malnourished infants (6-23 months) and children (24-59 months) from 13 villages. The RUSFs contained either 478 (mothers, children) or 239 kcal/d (infants) with 15% or 33% of protein from dairy and were distributed at community health centers 5 d/wk. Controls were wait-listed to receive RUSF. Primary outcomes were mid-upper arm circumference (MUAC) in mothers, and weight-for-age and height-for-age z -scores (WAZ and HAZ) in infants and children. Results: There was a significant effect of the RUSF-33% on MUAC in mothers ( P = .03). The WAZ and HAZ increased substantially, by ≈1 z -score, in infants and children ( P < .01) independent of group randomization. In children, but not infants, baseline WAZ and change in maternal MUAC were associated with change in WAZ (β = .07, P = .02). Conclusion: Ready-to-use supplementary foods with higher dairy protein content had a significant benefit in village mothers, supporting a comparable recent finding in preschool children. In addition, supplementation of children <2 years resulted in improved growth independent of family nutritional status, whereas success in older children was associated with change in maternal nutrition, suggesting the need for community-level education about preventing malnutrition in older, as well as younger, children.